2011
DOI: 10.1002/ajh.21932
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐ and beta‐synucleins are new diagnostic tools for acute erythroid leukemia and acute megakaryoblastic leukemia

Abstract: b b-thalassemias are characterized by an imbalance of globin chains with an excess of a-chains which precipitates in erythroid precursors and red blood cells (RBCs) leading to inefficient erythropoiesis. The severity of the disease correlates with the amount of unpaired achains. Our goal was to develop a simple test for evaluation of the free a-hemoglobin pool present in RBC lysates. Alpha-Hemoglobin Stabilizing Protein (AHSP), the chaperone of a-Hb, was used to trap excess aHb. A recombinant GST-AHSP fusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…Maturation of megakaryocytes leads to increased expression of α-synuclein with a concomitant down-regulation of β-synuclein (Hashimoto et al, 1997). Consistent with these findings, α-synuclein has been shown to be expressed by blasts of acute erythroid leukemia and acute megakaryoblastic leukemia, whereas its expression is reduced in megakaryocytes of myeloproliferative disorders (Maitta et al, 2011). Expression of β-synuclein, on the other hand, is noted only in the blasts of acute megakaryoblastic leukemia (Maitta et al, 2011).…”
Section: Introductionsupporting
confidence: 54%
“…Maturation of megakaryocytes leads to increased expression of α-synuclein with a concomitant down-regulation of β-synuclein (Hashimoto et al, 1997). Consistent with these findings, α-synuclein has been shown to be expressed by blasts of acute erythroid leukemia and acute megakaryoblastic leukemia, whereas its expression is reduced in megakaryocytes of myeloproliferative disorders (Maitta et al, 2011). Expression of β-synuclein, on the other hand, is noted only in the blasts of acute megakaryoblastic leukemia (Maitta et al, 2011).…”
Section: Introductionsupporting
confidence: 54%
“…CLPs can differentiate into T, B and natural killer (NK) cells but not myeloid cells, while CMPs give rise to all myeloid lineage cells via megakaryocyte/ erythrocyte (MEPs) or granulocyte/macrophage progenitors (GMPs). It was recently shown that α-synuclein is present in megakaryocytes, platelets, erythroid precursors, and erythrocytes, while its expression is reduced in megakaryocytes of myeloproliferative neoplasms (Maitta et al, 2011). Moreover, it was found to be a specific marker of acute megakaryoblastic leukemia subtype M7 (AML M7) suggesting that α-synuclein could play a role in the pathogenesis of some hematological neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…4,23 Using immunohistochemical staining of normal bone marrow, we have recently confirmed and extended these observations to neoplastic bone marrow, where a-synuclein was expressed by erythroid precursors in acute erythroid leukemia and by megakaryoblasts in acute megakaryoblastic leukemia, but not by myeloblasts in acute myeloid leukemia. 18 In contrast, we detected g-synuclein in the endothelial cells lining the sinuses and blood vessels of the bone marrow but not in any hematopoietic cell lineages. 18 Although the expression of g-synuclein by vascular endothelial cells has been described in nonlymphoid tissues, 17 the tumors of lymphatic and vascular origin have not been studied.…”
mentioning
confidence: 52%
“…18 In contrast, we detected g-synuclein in the endothelial cells lining the sinuses and blood vessels of the bone marrow but not in any hematopoietic cell lineages. 18 Although the expression of g-synuclein by vascular endothelial cells has been described in nonlymphoid tissues, 17 the tumors of lymphatic and vascular origin have not been studied. Therefore, we immunohistochemically stained a comprehensive panel of benign and malignant lymphoid tissues and spindle cell neoplasms (SSNs) for the expression of g-synuclein.…”
mentioning
confidence: 52%